Is primary Sjögren’s syndrome a risk factor for malignancies different from lymphomas? What does the literature highlight about it? - Ciro Manzo; Melek Kechida (Rheumatology, 2017)
Background : Primary Sjögren’s syndrome (pSS) is a chronic systemic autoimmune disease with an elevated risk of developing lymphoproliferative malignancies (LM). Whether pSS is a risk factor or not for non-lymphoma malignancies (NLM) has been scarcely evaluated in the literature. Age is per se a risk factor for malignancies: patients over 70 years old have 4 times higher risk for cancers than adults. Even if the mean age of pSS onset usually is in the 4th and 5th decade, its onset in patients aged over 65 years (Elderly Onset pSS – EOpSS) is not uncommon. Material and methods : To evaluate pSS as a risk factor for NLM we performed a systematic electronic search on PubMed in the period 2006–2016 to identify all the publications on this topic. The studies were eligible for inclusion if they reported specific Standardized Incidence Ratio (SIR) with 95% CI. Studies that did not report sufficient published and/or original data were excluded. Results : Only 7 articles of 494 that we found in PubMed fulfilled the inclusion criterion. In the vast majority of these, SIR values were not statistically significant for NLM. The occurrence of NLM after LM was statistically significant in some studies and a NLM represented the most frequent cause of death. The possibility that NLM may represent a paraneoplastic syndrome seems much more frequent than LM, the risk of which increases with time after the diagnosis. Data regarding the neoplastic weight of EOpSS are mainly pointed out by case reports. Conclusions : Primary Sjögren’s syndrome is not associated with an increased risk for NLM. However the possibility that NLM may appear after recovery from lymphoma should be carefully considered because it could be cause of the patient’s death. Similarly the possibility that NLM may represent a paraneoplastic syndrome must be highlighted. The relationship between EOpSS and SIRs for NLM should be deepened with studies on ad hoc cohorts.